Urban-Rural Differential in Literacy Rate: A Case Study of Punjab: Exploring the Educational Disparities in Punjab (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Lietracy attainment is essential for the development of any person, society, and nation. It empowers the persons to know their environments and also transforms the mirror of society. The level of educational attainment is one of the vital indicators for the measurement of the development of society. In the 21st century, society who is well educated equipped with a bundle of information, attitudes and computer skills is essential. The present paper is an attempt to study the patterns and their differentials of rural and urban in terms of literacy rate. Punjab in the terms of education status shows a better picture with the literacy rate of 76.68 per cent as per 2011 census. The rank of Punjab is dropped down from 16th position 2001 to the 21st position at all India ranking of literacy in 2011. In this paper, the urban-rural differentials in literacy are measured out which shows the large differentials.